KEPASTIAN HUKUM MENGENAI BATAS TANGGUNG JAWAB DIREKSI ATAS TERJADINYA FRAUD DALAM PENGELOLAAN PERSEROAN TERBATAS - Efran Dippos M. Sinaga; Nur Hakim; Roni Pandiangan (CORPUS JURIS : JURNAL ILMU HUKUM, 2026)
This research is motivated by the absence of legal certainty regarding the scope of the Board of Directors' liability for fraud committed in the management of a Limited Liability Company. Although Law Number 40 of 2007 concerning Limited Liability Companies imposes fiduciary obligations upon directors to act in good faith, with due care, and in the best interests of the company, it does not provide clear legal parameters for determining when directors may be held personally liable for fraudulent conduct. This regulatory ambiguity has resulted in inconsistent legal interpretation and judicial application, particularly in distinguishing between legitimate business risks protected by law and unlawful conduct involving fault, abuse of authority, or fraud. This research employs the Theory of Legal Certainty and Theory of Legal Liability. This research adopts a normative legal research method using statutory, case, analytical, and conceptual approaches. The legal materials consist of primary, secondary, and tertiary legal sources collected through library research and analyzed qualitatively. The analysis focuses on the Indonesian Civil Code, Law Number 40 of 2007 concerning Limited Liability Companies as amended by Law Number 6 of 2023, together with relevant judicial decisions concerning the civil liability of directors in the management of Limited Liability Companies. The findings demonstrate that the personal liability of directors for fraud does not arise automatically merely because the company has suffered financial losses. Instead, such liability must be established through proof of fault, abuse of authority, negligence, or breach of fiduciary duties committed by the directors in performing their managerial functions. The research further reveals that the absence of explicit statutory provisions defining the scope of directors' liability for fraud has created legal uncertainty in judicial practice. Therefore, a consistent interpretation of the statutory provisions governing directors' liability is required by emphasizing the principles of good faith, due care, and corporate accountability in order to achieve a balanced legal framework that protects directors acting in accordance with the law while simultaneously ensuring legal certainty for the company, shareholders, creditors, and other affected stakeholders.